Prevalence and characteristics of aggressive periodontitis - Nariratih, Diatri; Rusjanti, Janti; Susanto, Agus (Padjadjaran Journal of Dentistry, 2011)
Aggressive Periodontitis is one of periodontal disease that generally affects individuals less than 30 years old, with a rapid attachment loss and alveolar bone destruction. Special features of the disease are affected incisors and first molars with symmetrical bilateral destruction. The purpose of this study was to determine the prevalence and characteristics of Aggressive Periodontitis at Student Clinics, Faculty of Dentistry Padjadjaran University on May to July 2010. Based on accidentally sampling, 415 new patients at Dental and Oral Hospital, Faculty of Dentistry Padjadjaran University and Dental and Oral Polyclinic at RSUP dr. Hasan Sadikin Bandung participated in this study. Each subject filled out the questionnaire and did a clinical examination. Patients with attachment loss â¥ 4 mm were referred for radiographic and microbiologic examination to support the diagnosis. The results showed that there were 13 patients who have the diagnostic criteria of Aggressive Periodontitis. Nine patients were diagnosed as Localized Aggressive Periodontitis, and 4 patients as Generalized Aggressive Periodontitis. It is concluded that the prevalence of Aggressive Periodontitis was 3.13%, and indicated low prevalence. Characteristics of Localized Aggressive Periodontitis patients were female in 20-29 age range, whereas characteristics of Generalized Aggressive Periodontitis patients were male in 30-39 age range.